1994
DOI: 10.1080/03014469400003482
|View full text |Cite
|
Sign up to set email alerts
|

Further blood genetic studies on Amazonian diversity—Data from four Indian groups

Abstract: Information related to 31 protein genetic systems was obtained for 307 individuals affiliated with the Cinta Larga, Karitiana, Surui and Kararaô Indians of northern Brazil. In terms of genetic distances the Cinta Larga showed more similarities with the Karitiana (both are Tupi-speaking tribes), while at a more distant level the Surui clustered with the Kararaô. The latter, a Cayapo subgroup, showed a completely different genetic constitution from the other subgroups of this same tribe. Both the Kararaô and Kar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 23 publications
4
19
0
2
Order By: Relevance
“…The average G ST value obtained at these loci in the Colombian Amerindians (0.0584) was very similar to that obtained in six Caribbean-speaking Indian groups from Brazil (0.059) by Callegari-Jacques et al [94], and lower to that calculated in another five Brazilian Amerinds, by using six VNTR's loci (0.129) by Zago et al [32].…”
Section: Genetic Heterogeneitymentioning
confidence: 65%
“…The average G ST value obtained at these loci in the Colombian Amerindians (0.0584) was very similar to that obtained in six Caribbean-speaking Indian groups from Brazil (0.059) by Callegari-Jacques et al [94], and lower to that calculated in another five Brazilian Amerinds, by using six VNTR's loci (0.129) by Zago et al [32].…”
Section: Genetic Heterogeneitymentioning
confidence: 65%
“…A genetic basis for susceptibility and immunological response to rabies has been shown previously in mice 46–48. Although it is possible that certain isolated and remote populations in the Amazon region may be genetically and immunologically unique,49,50 two studies have also found signatures of gender-specific genetic admixture in certain Amazon populations and suggest that historical social policies have strongly influenced the migration of persons to and genetic mixing within the Amazon region 49,51. Genetic comparisons of immunological markers and relevant inducible responses (e.g., humoral and cellular response to rabies vaccination)52 from populations in urban areas and throughout the Amazon region of Perú may shed additional light on whether certain indigenous populations show evidence of natural selection for enhanced nonspecific or specific immunological responses and genetic resistance to rabies infection.…”
Section: Discussionmentioning
confidence: 99%
“…While this subhaplogroup may have origins in the first migrants that came into the continent directly moving from the Atlantic coast into the Amazon (Callegari-Jacques et al 1994;Salzano and Callegari-Jacques 1988), further data from other South American groups will reveal whether it remains restricted to the region.…”
Section: Discussionmentioning
confidence: 99%